Strategi Komunikasi Pemasaran Brand Itswooni dalam Membangun Brand Awareness - Wisely, Erica; Rusdi, Farid (Prologia, 2025)
ItsWooni is one of the local brands that recently entered the competition in 2022, offering a complementary addition to fashion through its product line of bags. The aim of this research is to understand the marketing communication strategies employed by the ItsWooni brand to enhance brand awareness. Marketing communication in this context is carried out through influencer marketing and content marketing. In this study, the researcher adopts a qualitative approach and a case study method. Data is gathered through in-depth interviews, non-participant observation, and documentation. Interviews are conducted with the owner, team, and customers of ItsWooni to gain a comprehensive understanding of the brand. Meanwhile, observation involves examining and analyzing data and information related to ItsWooni. The findings of this research reveal the strategies employed in marketing communication to build and sustain brand awareness. ItsWooni merupakan salah satu brand lokal yang baru saja bersaing di tahun 2022 yang dapat menjadi pelengkap busana karena produk yang dikeluarkan oleh ItsWooni adalah tas. Tujuan penelitian ini adalah untuk mengetahui bagaimana strategi komunikasi pemasaran yang dilakukan oleh brand ItsWooni dalam meningkatkan kesadaran merek. Komunikasi pemasaran ini dilakukan melalui influencer marketing dan content marketing. Dalam penelitian ini, peneliti menggunakan pendekatan kualitatif dan metode studi kasus. Peneliti memperoleh data melalui wawancara mendalam, observasi non partisipan dan dokumentasi. Wawancara dilakukan bersama pemilik, team dan customer ItsWooni untuk mengetahui secara mendalam mengenai ItsWooni. Sementara itu, observasi dilakukan dengan mengamati, menganalisis data dan informasi mengenai ItsWooni. Hasil temuan dari penelitian ini adalah mengetahui bagaimana strategi komunikasi pemasaran dalam membangun dan mempertahankan kesadaran merek.